Pengaruh Store Atmoshpere, Lokasi dan Variasi Produk Terhadap Keputusan Pembelian pada coffee shop Kopi Dent Pariaman - Cherrysa Denis Monica; Rose Rahmidani (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2023)
This research aims to analyze how customers' perceptions of the atmosphere, location and product variations of the Kopi Dent coffee shop influence their purchasing decisions. his research is causative research. The research population is members of the Kota Pariaman community. This research involved 97 respondents who met the criteria of having visited the Kopi Dent coffee shop in Pariaman, who were selected using the purposive sampling method. This research uses primary data collected through distributing questionnaires to people in Pariaman who meet certain criteria. The analysis technique uses SPSS 26 and multiple regression analysis. The research results show that (1) Store atmosphere, product variety and location have a positive and significant effect on purchasing decisions. (2) The store environment has a positive and large influence on purchasing choices. (3) Purchase choices are greatly influenced by location. (4) Having a wider choice will influence consumer choices positively and significantly.